Collaborative Governance Pengelolaan Sampah Kang Pisman di Kecamatan Kiaracondong Kota Bandung - Rikhard Candra; Erliana Hasan; Dedeh Maryani (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This article analyzes collaborative governance in waste management through the Kang Pisman program in Kiaracondong District, Bandung City. The study is important because urban waste management cannot rely only on collection and transportation, but requires coordinated roles among government, business actors, community organizations, waste banks, and residents. This study used a descriptive qualitative approach by adapting thesis-based field data into a journal article format and updating relevant literature from 2018 onward. Data were obtained through interviews, observation, documentation, and reanalysis based on four dimensions: starting conditions, institutional design, facilitative leadership, and collaborative process. The findings show that Kang Pisman has encouraged waste reduction, separation, and utilization, but collaboration in Kiaracondong has not yet formed an integrated and continuous model. The main barriers include uneven community understanding, limited operational facilities, inconsistent socialization, weak stakeholder forums, and limited monitoring at neighborhood level. Community participation increases when waste banks, local cadres, and neighborhood institutions are active. The study recommends strengthening formal multi-stakeholder forums, data-based planning, practical household education, clear role distribution, and integration between waste banks, private partners, and local government.